2022
DOI: 10.1039/d2dt00166g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and properties of palladium(ii) complex of α-formyl pyrrolyl dipyrromethene

Abstract: A simple α-formyl pyrrolyl dipyrromethene ligand was synthesized by deboronation of BF2-complex of α-formyl pyrrolyl dipyrrin under Lewis acid-catalyzed conditions. The α-formyl pyrrolyl dipyrrin ligand was treated with PdCl2 in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…To prepare Ru­(II)-α-formyl 3-pyrrolyl BODIPY complex 6 , we first prepared the required ligand, α-formyl 3-pyrrolyl BODIPY 3 , by treating 3-pyrrolyl BODIPY 2 with POCl 3 in DMF/DCE under Vilsmeier-Haack reaction conditions. , Compound 3 was then treated with [Ru­( p -cymene)­Cl 2 ] 2 in toluene in the presence of a base at reflux for 3 h followed by recrystallization to afford Ru­(II)-α-formyl 3-pyrrolyl BODIPY 6 in 40% yield (Scheme ). Compound 3 was also treated with 2-aminophenol in ethanol at reflux for 4 h followed by recrystallization to afford 3-pyrrolyl BODIPY-Schiff base compound 9 by our recent publication .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare Ru­(II)-α-formyl 3-pyrrolyl BODIPY complex 6 , we first prepared the required ligand, α-formyl 3-pyrrolyl BODIPY 3 , by treating 3-pyrrolyl BODIPY 2 with POCl 3 in DMF/DCE under Vilsmeier-Haack reaction conditions. , Compound 3 was then treated with [Ru­( p -cymene)­Cl 2 ] 2 in toluene in the presence of a base at reflux for 3 h followed by recrystallization to afford Ru­(II)-α-formyl 3-pyrrolyl BODIPY 6 in 40% yield (Scheme ). Compound 3 was also treated with 2-aminophenol in ethanol at reflux for 4 h followed by recrystallization to afford 3-pyrrolyl BODIPY-Schiff base compound 9 by our recent publication .…”
Section: Resultsmentioning
confidence: 99%
“…We also showed that the α-position of the appended pyrrole can be easily functionalized with functional groups such as −CHO 3 , and the functionalized meso -aryl 3-pyrrolyl BODIPYs have been used to synthesize several interesting fluorescent 3-pyrrolyl BODIPY-based conjugates . In due course of time, we and others have also developed a Lewis acid-catalyzed route to demask the BF 2 unit from BODIPYs, 3-pyrrolyl BODIPYs, and other BF 2 -complexes under very simple reaction conditions. Thus, tripyrrolic meso -aryl-pyrrolyl dipyrrins 4 are now easily available as ligands to explore their potential to form coordination complexes. , A perusal of the literature revealed that the dipyrrins and their derivatives have been used extensively as ligands for coordination chemistry, but the reports on tripyrrolic ligands and higher analogues or their derivatives are very few. In this paper, we used 3-pyrrolyl BODIPY 2 and α-formyl 3-pyrrolyl BODIPY 3 as key precursors to prepare one example of Ru­(II) complex 5 and three examples of BODIPY-Ru­(II) complexes 6 – 8 (Figure ) and explored their structure and spectral and redox properties using various experimental and theoretical methods. We have chosen 3-pyrrolyl BODIPY-based ligands which have the appended pyrrole “N” and either “O” of functionalized group as in 3 or “N” of substituent present at the α-position of appended pyrrole as in 9–10 to coordinate with Ru­(II) ion to form BODIPY-Ru­(II) complexes 6–8 .…”
Section: Introductionmentioning
confidence: 96%
“…The crude product was purified by silica gel column chromatography eluting with petroleum ether/ethyl acetate (70 : 30) and pure α-acrylaldehyde 3pyrrolyl BODIPY 3 was obtained as a blue solid in 67 % yield (77 mg). 3 Hz, 1H), 6.63-6.58 (m, 1H), 6.56 (dd, J = 3.7, 1.7 Hz, 1H), 2.49 (s, 3H), 13 C NMR (101 MHz, CDCl 3 ) δ 192. 6, 189.8, 148.1, 142.6, 140.8, 139.8, 139.7, 137.7, 134.6, 134.2, 133.7, 132.6, 131.2, 130.5, 129.1, 128.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] This is because of their ease of synthesis, flexibility, and very attractive physicochemical properties, which can be tuned at will by suitable modifications. A few years back, we [9][10][11][12][13][14] and others [15][16][17][18][19] introduced a five membered pyrrole unit at the α-position of the BODIPY to form 3-pyrrolyl BODIPY 1. The pyrrolyl group at the α-position of BODIPY in 3-pyrrolyl BODIPY significantly alters the electronic properties as π-conjugation is extended and 3-pyrrolyl BODIPYs absorb and fluoresce at longer wavelength region with more quantum yields compared to BODIPYs.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that the BF 2 unit of 3-pyrrolyl BODIPYs could also be demasked by treating 3-pyrrolyl BODIPYs with Lewis acids such as AlCl 3 and ZrCl 4 to afford tri-pyrrolyl ligands that can be used to prepare interesting coordination complexes such as 3. [15][16][17][18] Recently, we reacted the 3-pyrrolyl BODIPY with acetone under acid-catalyzed conditions to afford bis(3-pyrrolyl BODIPY) 4, which was then treated with AlCl 3 to demask the BF 2 units to obtain a hexapyrrolic ligand, that was then used to synthesize bis(Cu(II)/Zn(II)) helicates 5 and explored their structures, and spectral and electrochemical properties. 19,20 In continuation of our work on 3-pyrrolyl BODIPYs, herein, we used meso-( p-formylphenyl) 3-pyrrolyl BODIPY 8 8 as a key precursor to synthesize two very novel closely coupled tris(BODIPY)s 6 and 7 over a sequence of synthetic steps and explored their structures and properties.…”
Section: Introductionmentioning
confidence: 99%